PRAKTIK POLIANDRI DI DESA PANTAI CERMIN KECAMATAN TAPUNG KABUPATEN KAMPAR - Rudianto Hutagalung; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Polyandry is a form of marriage that is contrary to conscience and human nature, even contrary to health. For polyandry is a form of marriage in which a woman (wife) was married to multiple husbands, so that a wife can have multiple partners (husband). Within Islam, marriage is prohibited polyandry.The problems discussed in this research is, whether the factors that led to the practice of polyandry in the coastal village of mirrors, Tapung subdistrict, Kampar. How are the legal consequences arising from the practice of polyandry in the coastal village of mirror toward marriage,basedLaw Number. 1 Year 1974 About Marriage and Islamic Law Compilation. In this study, using juridical empirical legal research. The meaning of juridical empirical research is an attempt to approach the issues examined by the nature of the law, or in accordance with the reality of life in the community. In addition to the juridical empirical research, the nature of the research is descriptive research which aims to provide a more precise picture and the concrete practice of polyandry in the coastal village of mirrors, Tapung subdistrict, Kampar district. The results showed that the practice of polyandry in the coastal village Tapung District of Kampar regency mirror is an unlawful act either in law or religion. Because in the Act nor the religion forbids polyandry.Keywords: Praktik- marriage is Polyandry